Self‐reported care needs of Dutch homeless people with and without a suspected intellectual disability: a 1.5‐year follow‐up study. (1st October 2015) - Van Straaten, Barbara; Rodenburg, Gerda; Van der Laan, Jorien; Boersma, Sandra N.; Wolf, Judith R.L.M.; Van de Mheen, Dike
Abstract: Cognitive impairment is a prevalent problem among the homeless and seems related to more psychosocial problems. However, little is known about the care needs of the subgroup of homeless people with an intellectual disability compared to those without an intellectual disability and how their care needs develop over time. This study explores self‐reported care needs within a broad range of life domains among Dutch homeless people with and without a suspected intellectual disability to gain insight into the transition of self‐reported care needs from baseline to follow‐up in both subgroups. This longitudinal study is part of a cohort study among homeless people who had been accepted for an individual programme plan in four major Dutch cities. The initial cohort consisted of 513 participants who were interviewed in 2011. At 1.5‐year follow‐up, 336 participants (65.5%) were also interviewed and screened for intellectual disability. Of these participants, 31% (95% CI 26.2–36.1) had a suspected intellectual disability. For both groups, between baseline and follow‐up, the number of 'unmet care needs' decreased significantly and the number of 'no care needs' increased significantly, while at follow‐up, participants with a suspected intellectual disability reported 'no care needs' on significantly fewer life domains than those without a suspected intellectual disability (mean numbers 16.4 vs. 17.5). Between baseline and follow‐up, 'met care needs' decreased significantly on housing for both groups, and increased on finances and dental care for participants with a suspected intellectual disability. At follow‐up, participants with a suspected intellectual disability more often preferred housing support available by appointment than those without a suspected intellectual disability. These findings suggest that homeless people who had been accepted for an individual programme plan with a suspected intellectual disability have care needs for a longer period of time than those without a suspected intellectual disability. Providing care to homeless people with a suspected intellectual disability might require ongoing care and support, also after exiting homelessness. Support services should take this into account when considering their care provision and planning of services.